IMPACT OF PIRACY AND SEA ROBBERIES ON FISHING BUSINESS IN NIGERIA: A FOCUS ON LAGOS COASTAL AREA - Abdullahi Saheed USMAN; Oluwaseyi Joseph AFOLABI; NWOYE Casmier Friday (Business Excellence and Management, 2019)
Nigeria as a littoral state with a coastline of slightly above 800 kilometers and located in the Gulf of Guinea (GoG) region puts the government in a position that requires her to deploy resources to combat the menace of piracy and sea robbery. Pirate activities affected not only the maritime transport sector, but the other forms of maritime economic activities. The fishing industry also got her fair share of this menace despite the contribution of the industry to the society. The activities of pirates and sea robbers and their impacts on fishing industry in Lagos coastal area was investigated using structured questionnaire deployed to relevant stakeholders in the fishing business in Lagos area. This research interrogates possible factors that create the enabling environment for piracy to flourish. The study revealed that the inability of government to effectively curb activities of these criminals was to some extent influenced by corruption, poverty and inequality in the society. Financial loss to the nation due to the menace was found to be alarming and has forced several fishing companies out of business to the extent that only few fishing vessels (trawlers) are currently in operation in the area of study. The research confirmed negative effects of piracy on sea businesses, particularly fishing activities, which was the crux of this investigation. The study recommends, amongst others, the Nigerian government should evolve sound resource management and equitable allocative practices to leverage the enormous natural resources and oil affluence to effectively address the cacophony of economic afflictions and legal framework should be revisited, reviewed, reformed and harmonized.